MODEL GERAKAN DAKWAH DI INDONESIA - Nahdatunnisa Asry (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstractDa'wah is the delivery of Islamic teachings can be in the form of amar makruf and nahi munkar. The pattern of da'wah can take the form of cultural propaganda, political preaching, and economic da'wah. Efforts to implement or ground social monotheism supported by four doctrines also live in Muhammadiyah circles. The doctrine is the doctrine of enlightenment of the people, the doctrine of encouraging pious charity, the doctrine of cooperation for virtue, the doctrine of not practicing politics. Da'wah is not understood as a tabligh, but a massive movement on various aspects of human life. Muhammadiyah balances the spirituality of da'wah with social charity as a real movement in response to the problems of the ummah at various levels.Keyword: Da’wah, Muhammadiyah, Case Study.